2008
DOI: 10.2119/2007-00059.saiki
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Marker Genes for Differential Diagnosis of Chronic Fatigue Syndrome

Abstract: Chronic fatigue syndrome (CFS) is a clinically defined condition characterized by long-lasting disabling fatigue. Because of the unknown mechanism underlying this syndrome, there still is no specific biomarker for objective assessment of the pathological fatigue. We have compared gene expression profiles in peripheral blood between 11 drug-free patients with CFS and age-and sexmatched healthy subjects using a custom microarray carrying complementary DNA probes for 1,467 stress-responsive genes. We identified 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
71
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(74 citation statements)
references
References 24 publications
2
71
0
1
Order By: Relevance
“…For example, Brenu and colleagues [12] have conducted multiple biomarker studies with CFS patients and have reported increased anti-inflammatory cytokines (i.e., IL-10) and the pro-inflammatory cytokines (i.e., TNF-alpha and IFN-gamma), which may also influence the cytotoxic ability of the NK cells, as the surface markers Granzyme A and B and Perforin are responsible for cytotoxicity and can fluctuate in patients with CFS [12, 13, 15, 37]. Other researchers have reported increased expression of the CD69 marker and decreased expression of the CD25 surface marker in patients with CFS [10], which our study did not measure.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Brenu and colleagues [12] have conducted multiple biomarker studies with CFS patients and have reported increased anti-inflammatory cytokines (i.e., IL-10) and the pro-inflammatory cytokines (i.e., TNF-alpha and IFN-gamma), which may also influence the cytotoxic ability of the NK cells, as the surface markers Granzyme A and B and Perforin are responsible for cytotoxicity and can fluctuate in patients with CFS [12, 13, 15, 37]. Other researchers have reported increased expression of the CD69 marker and decreased expression of the CD25 surface marker in patients with CFS [10], which our study did not measure.…”
Section: Discussionmentioning
confidence: 99%
“…[25] The proteasome is the central proteolytic system that also plays an important role in the major histocompatibility complex-class I antigen processing. [26] PSMA4 is a component of the Adenosine Triphosphate-and ubiquitin-dependent nonlysosomal pathway, and it is involved in the processing of class I major histocompatibility complex peptides. [20] PSMA4 has a role in modulating human lung cancer cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…GZMA and GZMB have been shown to be decreased in CFS/ME patients [7,29]. GZMB is an important marker of susceptibility to influenza in older adults [30].…”
Section: Discussionmentioning
confidence: 99%